Digital Sufism: Representation of Surah Al-Maidah: 83-85 in the Lyrics of the Song "Tafsir Cinta" by Panji Sakti - Faizah, Faizah Munjata Salma; Faizah Munjata Salma; Kholila Mukaromah; Syarafina Azatul Hidayah (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2024)
The digital era has brought significant changes to various aspects of human life, including the fields of education and the dissemination of Islam. In this context, digital Sufism is often promoted as an appealing approach to spreading Islamic values. One of Indonesia's famous poets and singers, Panji Sakti, has successfully integrated Sufi values into contemporary music. This is evident from the elaboration of messages from Quranic verses in the lyrics of songs popularized through digital media. One of his songs, titled "Tafsir Cinta," contains lyrics that romanticize the love between God and His servant. This study aims to explore the aspects of Sufism present in the song's lyrics. The research is directed at examining how Panji Sakti conveys the Sufi message from QS. al-Mā’idah: 83-85 in a song and its impact on religious practices in the digital era. This study involves library research. Discourse analysis is used to understand how Sufi messages are conveyed and interpreted in the digital context. The research also employs the living Qur'an perspective to explore the values of the Qur'an in the song lyrics. The results of this study show that the contents of this song match up with the message and meaning of QS. al-Mā’idah: 83–85. That ayah and the song have a common characteristic, which is to regard tears as a symbol of human intimacy with God. This song has had over 1.7 million plays on Spotify, 543 million views on YouTube, and thousands of views on Instagram and Tiktok. The findings of this study are expected to contribute to the understanding of the importance of digital media, such as contemporary music, as a means of spreading Islam to reach a wider audience, especially among the younger generation.